Capital of Feedback - Nina Stener Jørgensen (Footprint)
The body of work by British architect Cedric Price (1934–2003) is largely concerned with architecture’s relationship to technology and its impact on society. As contemporary architecture finds itself confronted with similar issues today, Price’s designs are being revisited and hailed for their prospective and inventive visions. As such, it seems timely to ask if Price’s designs can be regarded as precedents for future projects that aim to couple participation and technology through architectural design.